Historical Foundation of Game-Based Learning. Review of the prevailing game and learning theories of the early 20th century - Schorer, Antonia (Ludica. Annali di storia e civiltà del gioco, 2021)
The use of (digital) games for educational purposes is a promising endeavour in our modern world. The scientific interest in game- based learning and in serious games has a long and interdisciplinary history, especially at the beginning of the 20th century. A large part of the game and learning theories that are still considered valid today were developed or originated at this time. Even in our modern educational landscape, these theoretical foundations retain their significance and pave the way for a promising use of serious games and game-based learning. The article aids an in-depth understanding of the situation by identifying the various game- and learning-theory approaches advocated at the beginning of the 20th century and examining their points of connection. This discussion will show whether these paradigms function as the historical foundation of today’s learning games and whether they set the course for the use of games in education from today’s perspective.<br